Protein profiling and immunoinformatic analysis of the secretome of a metal-resistant environmental isolate Pseudomonas aeruginosa S-8 - Kumari, Kiran; Dey, Jyotirmayee; Mahapatra, Soumya Ranjan; Ma, Ying; Sharma, Parva Kumar; Misra, Namrata; Singh, Rajnish Prakash (Folia microbiologica, 2024)
The bacterial secretome represents a comprehensive catalog of proteins released extracellularly that have multiple important roles in virulence and intercellular communication. This study aimed to characterize the secretome of an environmental isolate Pseudomonas aeruginosa S-8 by analyzing trypsin-digested culture supernatant proteins using nano-LC-MS/MS tool. Using a combined approach of bioinformatics and mass spectrometry, 1088 proteins in the secretome were analyzed by PREDLIPO, SecretomeP 2.0, SignalP 4.1, and PSORTb tool for their subcellular localization and further categorization of secretome proteins according to signal peptides. Using the gene ontology tool, secretome proteins were categorized into different functional categories. KEGG pathway analysis identified the secreted proteins into different metabolic functional pathways. Moreover, our LC-MS/MS data revealed the secretion of various CAZymes into the extracellular milieu, which suggests its strong biotechnological applications to breakdown complex carbohydrate polymers. The identified immunodominant epitopes from the secretome of P. aeruginosa showed the characteristic of being non-allergenic, highly antigenic, nontoxic, and having a low risk of triggering autoimmune responses, which highlights their potential as successful vaccine targets. Overall, the identification of secreted proteins of P. aeruginosa could be important for both diagnostic purposes and the development of an effective candidate vaccine.
Keywords: bakteriální proteiny; Metals; CAZymes; Bacterial Proteins; Proteomics; Computational Biology; Secretome; proteomika; tandemová hmotnostní spektrometrie; Chromatography, Liquid; výpočetní biologie; LC–MS/MS; Pseudomonas aeruginosa; chromatografie kapalinová; kovy; sekretom; Tandem Mass Spectrometry